The Effect of the Discovery Learning Model on Student Biology Learning Outcomes on Human Digestive System Materials Class XI SMA Negeri 2 Tondano - Etin Ruban; Helen J. Lawalata; Zusje W. M. Warouw (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2024)
This study aims to determine the influence of the Discovery Learning learning model on the cognitive learning outcomes of students' biology on the material of the human digestive system in class XI of SMA Negeri 2 Tondano. With this research method, it is quasi-experiment research. The result is a significance value (2-tailed) < 0.05, then H0 is rejected and H1 is accepted. In the results of the